Complications in 2200 consecutive laparoscopic radical prostatectomies: standardised evaluation and analysis of learning curves - Fiedler, Marcel; Weiß, Hagen O.; Pini, Giovannalberto; Goezen, Ali S.; Schulze, Michael; Teber, Dogu; Rassweiler, Jens J. (European urology, 2010)
Background - Laparoscopic radical prostatectomy (LRP) represents an established treatment modality for localised prostate cancer. - Objective - To report standardised complication rates for LRP, evaluate the development of complication rates over time, and show changes within the learning curves of laparoscopic surgeons. - Design, setting, and participants - We conducted a standardised analysis of 2200 consecutive patients who underwent LRP between 1999 and 2008 at a single institution. - Intervention - LRP was performed using a transperitoneal (n=871) or extraperitoneal (n=1329) retrograde Heilbronn technique. Five surgeons operated on 96% of the patients. - Measurements - Complications were classified according to the modified Clavien system. Total complication rates and changes over time were analysed. Three generations of surgeons were defined for evaluation of learning curves. - Results and limitations - Minor complications occurred in 21.7% of patients (Clavien 1: 6.8%; Clavien 2: 14.9%); anaemia requiring transfusion (10.4%) dominated. Early reinterventions were necessary in 6.7% of patients (Clavien 3a: 3.6%; Clavien 3b: 1.5%; Clavien 4a: 1.5%; Clavien 4b: 0.1%). Late Clavien 3b complications occurred in 4.7% of patients—most of them anastomotic strictures. Mortality was 0.1% (Clavien 5). There was a significant decrease in overall complication rates over time, resulting predominantly from decreasing Clavien 1-2 events. Learning curves of third-generation surgeons plateaued earlier compared to the first generation (250 vs 700 cases). The limitation of this study is that data concerning comorbidity were not included. - Conclusions - LRP is a safe procedure characterised by an acceptable profile of complications. Specifically, few major complications are reported. According to the complication rates, the learning curve of third-generation surgeons is significantly shorter compared to first- and second-generation surgeons.